Peloptulus (Peloptulus) phaeonotus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Peloptulus (Peloptulus) phaeonotus (C.L. Koch, 1844) Material – One specimen in Köçekli Village, Taşköprü forest, N 41° 24′ 05.84′′, E 34° 22′ 30.42′′, alt. = 1193 m, 10 August 2018, tree bark and debris of P. sylvestris . Previous record in Turkey – Kayseri (Seniczak et al. 2014) Global distribution – Palaearctic. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 264, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Peloptulus; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Peloptulus phaeonotus; Phenopelopidae; Taxonomy; 15. Life on land